2008
DOI: 10.1590/s0103-50532008000700008
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon contents and distribution in sediments from the southeastern Brazilian coast (Guanabara Bay)

Abstract: As concentrações de black carbon (BC), assim como a contribuição relativa de BC para o total de carbono orgânico sedimentar, foram determinadas pela primeira vez na Baía de Guanabara. A quantificação de BC realizou-se por método térmico (CTO-375) e a de carbono orgânico por método de oxidação a seco. As concentrações de carbono orgânico apresentaram grande variabilidade entre as estações (0,82 a 10,3%), mas foi possível definir regiões distintas na Baía de acordo com parâmetros como granulometria do sedimento,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The heavy metal concentrations presented relatively low levels in the sediments. All the Igeo results confirmed the sediment from harbor site as "unpolluted to moderated polluted" for all the studied metals since the index remained between 0.59 and 0.76 [78][79][80][81][82][83][84][85] (Table 6).…”
Section: Oceanography and Fisheries Open Access Journalsupporting
confidence: 54%
“…The heavy metal concentrations presented relatively low levels in the sediments. All the Igeo results confirmed the sediment from harbor site as "unpolluted to moderated polluted" for all the studied metals since the index remained between 0.59 and 0.76 [78][79][80][81][82][83][84][85] (Table 6).…”
Section: Oceanography and Fisheries Open Access Journalsupporting
confidence: 54%
“…Overall, we found that the BC content down the length of the sediment cores drawn from the tropical/sub-tropical and temperate vegetated ecosystems was greater than the amount of BC in non–vegetated coastal sediments (~0.01–0.60% dry mass) 15 , 25 27 . For Little Swanport and Salut–Mengkabong, the BC content determined via CTO and NAO ranged between 0.01% and 1.39% dry mass (median 0.25%, n = 192).…”
Section: Resultsmentioning
confidence: 77%
“…The NAO is designed to isolate the more labile macro-chars originating from local fires, which includes other components within the more refractory char–soot continuum 17 , 45 . Modifications of the CTO method were based on the protocols for larger sample sizes: spreading samples thinly on a single rack of inverted crucible lids at 360 °C 46 instead of 375 °C, and using a slow temperature ramping rate (30 °C min −1 ) 27 to inhibit charring combustion within the muffle furnace (Carbolite, Model: CWF 1300). The precision of the CTO method was typically ± 8.99% ( n = 4), expressed as CV.…”
Section: Methodsmentioning
confidence: 99%
“…Black carbon has been proposed to be an important sink in the global carbon cycle. [15][16][17][18] Information on the chemical properties and biological stability of black carbon in soil is limited and more research is needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Black carbon has been proposed to be an important sink in the global carbon cycle. [15][16][17][18] Information on the chemical properties and biological stability of black carbon in soil is limited and more research is needed in this area.The most accepted theory on the origin of ABE is the anthropogenic evidence demonstrated through the activities of prehistoric humans. The observations of Neves et al 19 indicate that the social practices in settlements with ABE are still not fully understood and that ABE formation was a faster process than previously thought.…”
mentioning
confidence: 99%